Mathematics in the making : authoring ideas in primary classrooms - Mills, Heidi (Heinemann, 1996)
Mathematics in the Making demonstrates how teachers can help children become respected authors of their own mathematical ideas by emphasizing mathematics as a way of thinking. Mills, O'Keefe, and Whitin use the term "author" to convey the active, constructive, and exploratory role that children must assume if they are to become empowered mathematical thinkers. They draw comparisons with the authoring cycle by describing children in grades 1-3 who revise, collaborate, and make personal connections to mathematical situations.